PENGGUNAAN POLLARD DENGAN ASAM AMINO SINTESIS DALAM PAKAN AYAM PETELUR TERHADAP UPAYA PENINGKATAN KUALITAS FISIK TELUR - Nonok Supartini (Universitas Tribhuwana Tunggadewi, 2009)
The objective of the experiment was to elucidate the effect of pollard utilization on the layer diets and the addition of critical amino acid to produce the eggs with lower content of cholesterol. The experiment used in the study with 315 Lohman strain were randomly limited in to 7 treatments in 7 replications with 15 birds each. The treatments were: R0 (control diet without pollard and without critical of AA), R1 (10% pollard + 50% critical of AA), R2 (10% pollard + 100% critical of AA), R3 (20% pollard + 50% critical of AA), R4 (20% pollard + 100% critical of AA), R5 (30%pollard + 50% critical of AA), R6 (30% pollard + 100% critical of AA). The results showed that the utilization of pollard with amino acid addition had given no significant different on production and eggs quality. The exception result was in yolk color had significantly different. It can be concluded that the treatment of 30% with amino acid addition resulted better production and egg quality